Mujeres Públicas: Feminism, Art and Biopolitics - Lucero Olguín, Olga María (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2019)
Our interest in this inquiry is to think about some aesthetic materials produced by the feminist collective Mujeres Públicas (MP), while is possible to perceive their design and searches as a sounding box for different questions that biopolitics, feminist thinking and visual and performative artistic activism enable. In this way, we analyze some of their productions, paying attention in how MPs think about power and how it operates on the women’s bodies, due to some evidence suggest that the collective artists' view of the power and the own operation of power that oppresses women, is changing and displacing. In the same way, the types of resistance that oppose to the power goes on mutating.